Liposomal Formulation of Hydroxychloroquine Can Inhibit Autophagy In Vivo - Wieslawa H. Dragowska; Jagbir Singh; Mohamed Wehbe; Malathi Anantha; Katarina Edwards; Sharon M. Gorski; Marcel B. Bally; Ada W. Y. Leung (Pharmaceutics)
Background/Objectives: Preclinical studies have shown that the anti-malarial drug hydroxychloroquine (HCQ) improves the anti-cancer effects of various therapeutic agents by impairing autophagy. These findings are difficult to translate in vivo as reaching an effective HCQ concentration at the tumor site for extended times is challenging. Previously, we found that free HCQ in combination with gefitinib (Iressa®, ZD1839) significantly reduced tumor volume in immunocompromised mice bearing gefitinib-resistant JIMT-1 breast cancer xenografts. Here, we sought to evaluate whether a liposomal formulation of HCQ could effectively modulate autophagy in vivo and augment treatment outcomes in the same tumor model. Methods: We developed two liposomal formulations of HCQ: a pH-loaded formulation and a formulation based on copper complexation. The pharmacokinetics of each formulation was evaluated in CD1 mice following intravenous administration. An efficacy study was performed in immunocompromised mice bearing established JIMT-1tumors. Autophagy markers in tumor tissue harvested after four weeks of treatment were assessed by Western blot. Results: The liposomal formulations engendered ~850-fold increases in total drug exposure over time relative to the free drug. Both liposomal and free HCQ in combination with gefitinib provided comparable therapeutic benefits (p > 0.05). An analysis of JIMT-1 tumor tissue indicated that the liposomal HCQ and gefitinib combination augmented the inhibition of autophagy in vivo compared to the free HCQ and gefitinib combination as demonstrated by increased LC3-II and p62/SQSTM1 (p62) protein levels. Conclusions: The results suggest that liposomal HCQ has a greater potential to modulate autophagy in vivo compared to free HCQ; however, this did not translate to better therapeutic effects when used in combination with gefitinib to treat a gefitinib-resistant tumor model.